Do consumers of manufactured cigarettes respond differently to price changes compared with their Roll-Your-Own counterparts? Evidence from New Zealand. Issue 3 (20th November 2013) - Tait, Peter; Rutherford, Paul; Saunders, Caroline
Abstract : Background: Price-based mechanisms are an important tobacco cessation policy tool in New Zealand (NZ) and so measurement of smokers' reaction to price changes is crucial in determining efficacy of this approach. Although approximately two-thirds of NZ tobacco demand is for manufactured cigarettes (MC) and one-third is for Roll-Your-Own (RYO) tobacco, previous price elasticity estimates have ignored differences between RYO tobacco and MC consumers. Methods: We employ a seemingly unrelated regression econometric approach applied to quarterly data over the period 1991–2011 to estimate price elasticities of demand separately for MC and RYO tobacco. Results: Estimate of price elasticity of demand for MC is −1.033, and −0.441 for RYO tobacco. RYO tobacco is an inferior good; a 1% increase in average weekly income is associated with a 0.8% reduction in demand. RYO tobacco is a substitute for MC; a 1% increase in the price of MC is associated with a 0.867% increase in demand for RYO tobacco. Conclusions: There is significantly different price responsiveness across the two tobacco product types. MC smokers react far more strongly to price increases compared with RYO tobacco smokers. These findings suggest that pricing mechanisms may be more effective for reducing MC demand than for RYO tobacco. However, substitution between products means that this pricing effect is muted by the uptake of RYO tobacco use. Cessation policy specific to RYO use should be designed to target this growing group.